2010
DOI: 10.2319/031010-139.1
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal blood flow changes due to rapid maxillary expansion

Abstract: Objective: To determine the pulpal blood flow (PBF) changes in anchorage teeth associated with the high forces of a rapid maxillary expansion (RME) appliance. Materials and Methods: The study was performed with 14 girls and 7 boys for a total of 21 patients between 10 and 15 years of age (mean, 13.1 6 1.39 years). A modified acrylic bonded RME appliance was used as an expansion appliance. Laser Doppler flowmetry was used for the pulpal perfusion measurements. Records were taken from 42 upper central incisors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(85 citation statements)
references
References 32 publications
5
72
1
7
Order By: Relevance
“…Application of the inclusion and exclusion criteria and follow-up on the referred studies identified 30 relevant publications (Figure 1). [3][4][5][6][7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Heterogeneity of the results of the investigations with similar technique of maxillary expansion was high (.85%). A meta-analysis was not performed for this reason.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Application of the inclusion and exclusion criteria and follow-up on the referred studies identified 30 relevant publications (Figure 1). [3][4][5][6][7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Heterogeneity of the results of the investigations with similar technique of maxillary expansion was high (.85%). A meta-analysis was not performed for this reason.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis was not performed for this reason. Twenty-one studies 3,4,6,8,9,15,[18][19][20][22][23][24][25][26][28][29][30][31][32][33][34] were retrospective, five studies 7,11,12,16,17 were prospective, and four studies 5,10,21,27 were prospective and randomized. Six studies 10,18,[22][23][24]33 compared the results with a control group of the same age, and eight studies 4,6,10,12,22,[32][33][34] analyzed the long-term effects of RME.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations